Promising therapeutic effects of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) in addressing autism spectrum disorder induced by valproic acid - Afshari, Masoud; Gharibzadeh, Shahriar; Pouretemad, Hamidreza; Roghani, Mehrdad (Frontiers in Neuroscience, 2024)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental condition that affects various regions of the brain. Repetitive transcranial magnetic stimulation (rTMS) is a safe and non-invasive method utilized for stimulating different brain areas. Our objective is to alleviate ASD symptoms using high-frequency rTMS (HF-rTMS) in a rat model of ASD induced by valproic acid (VPA).MethodsIn this investigation, we applied HF-rTMS for ASD treatment, focusing on the hippocampus. Behavioral assessments encompassed core ASD behaviors, as well as memory and recognition tests, alongside evaluations of anxiety and stress coping strategies. Additionally, we analyzed oxidative stress and a related inflammation marker, as well as other biochemical components. We assessed brain-derived neurotrophic factor (BDNF), Microtubule-associated protein-2 (MAP-2), and synaptophysin (SYN). Finally, we examined dendritic spine density in the CA1 area of the hippocampus.ResultsThe results demonstrated that HF-rTMS successfully mitigated ASD symptoms, reducing oxidative stress and improving various biochemical factors, along with an increase in dendritic spine density.DiscussionCollectively, our data suggests that HF-rTMS may effectively alleviate ASD symptoms. These findings could be valuable in clinical research and contribute to a better understanding of the mechanisms underlying ASD.